Penggunaan COBIT 2019 I&T Risk Management untuk Pengelolaan Risiko Transformasi Digital BankCo - Dewi, Yusnia Wilujeng Dwi Milenia; Mulyana, Rahmat; Santoso, Ari Fajar (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
Advances in information technology (IT) in the banking industry such as BankCo to implement digital transformation (TD). However, failures often occur in the implementation of TD due to poor IT governance. Therefore TD activities are regulated in PER-2/MBU/03/2023 concerning guidelines for corporate governance and the Indonesian Financial Services Sector Master Plan 2021-2025 concerning accelerating digital transformation. This research applies the DSR using the semi-structured interview method and design factor analysis using the COBIT 2019 Information and Technology Risk framework. The results of the design factor analysis resulted in prioritized IT management governance objectives (TKMTI) in the form of EDM03 Ensured Risk Optimization, APO12 Managed Risk, and APO02 Managed Strategy. Furthermore, an analysis of focus areas, preparation of recommendations, design of solutions, and roadmaps according to the seven components of governance were carried out, thus increasing the capability value by 0.6 (16.67%) from before the improvement. This research contributes to the knowledge base for related research, as well as being a reference for managing IT risk management for BankCo, as well as the banking industry in general.Keywords: Digital Transformation; IT Governance and Management; COBIT I&T Risk Management Focus Area; Design Science Research; Bank.Â AbstrakKemajuan teknologi informasi (TI) dalam industri perbankan seperti BankCo untuk melakukan implementasi transformasi digital (TD). Namun sering terjadi kegagalan dalam implementasi TD dikarenakan tata kelola TI yang kurang baik. Oleh karena itu kegiatan TD diatur dalam PER-2/MBU/03/2023 tentang pedoman tata kelola korporasi dan Master Plan Sektor Jasa Keuangan Indonesia 2021-2025 mengenai percepatan transformasi digital. Penelitian ini menerapkan DSR dengan metode wawancara semi terstruktur dan analisis faktor desain menggunakan kerangka kerja COBIT 2019 Information and Technology Risk. Hasil analisis faktor desain, menghasilkan prioritas tujuan tata kelola manajemen TI (TKMTI) berupa EDM03 Ensured Risk Optimization, APO12 Managed Risk, dan APO02 Managed Strategy. Selanjutnya dilakukan analisis fokus area, penyusunan rekomendasi, perancangan solusi, dan roadmap sesuai tujuh komponen tata kelola, hingga meningkatkan nilai kapabilitas sebesar 0,6 (16,67%) dari sebelum perbaikan. Penelitian ini berkontribusi pada basis pengetahuan untuk penelitian terkait, serta menjadi referensi pengelolaan manajemen risiko TI bagi BankCo, serta industri perbankan pada umumnya.Â